Towards the integrated didactics of Andalusian and American Spanish - Ramírez Quesada, Estrella (Didáctica. Lengua y Literatura, 2022)
Beyond the controversy, now overcome, around the so-called Andalusianism of Spanish in America, this paper presents a didactic proposal for secondary education to work on these varieties of Spanish in an integrated way. This favours a vision closer to the reality of linguistic variation and allows, through historical knowledge –a perspective often eliminated from the teaching of language in secondary school– to encourage an appreciation for linguistic diversity based on knowledge and not only in external factors. Thus, after the introduction and the theoretical framework that support the didactic proposal, there is a sequence of activities that can be carried out together or in isolation to work on Andalusian and American Spanish, as well as a series of conclusions among which it is worth highlighting the adaptability of the activities and resources to students of different levels and educational contexts.
Keywords: Andalusian varieties; American Spanish; Spanish language; teaching